Analysis of Differences Innovation in Regional Development Planning (Case Studies in South Sulawesi and West Sumatra Provinces) - Lily Latul (International Journal of Regional Innovation, 2021)
The existence of this technological development has become a medium used by a state administrator to improve welfare or services for its citizens. In need of an innovation that is used to capture this phenomenon. Local government innovation is very important in the process of implementing good and reliable governance (Good Govrnance). The implementation of regional development always begins with research and development activities, as well as assessment. Development planning is not only done on the table, without looking at the reality on the ground. The core problem of planning is in the planning process itself, which includes a series of procedures and involves many parties. The lengthy process and the many parties involved often make planning ineffective. Based on this, this study aims to analyze the differences in planning innovations carried out in two different regions, namely South Sulawesi and West Sumatra, to compare the innovations of the two regions. This study uses a qualitative descriptive approach. As a result, South Sulawesi and West Sumatra have different development innovations, in which South Sulawesi places more emphasis on improving website-based information systems which will become a reference for development planning, while West Sumatra emphasizes the assessment of construction services that will carry out development planning in the West Sumatra region. Suggestions in the future, each agency allocates a budget to increase the admin capacity of the SIPPD manager and provide cost consequences as motivation.